A Recurrent Suprapituitary Ependymal Cyst Managed by Endoscopy-Assisted Transsphenoidal Surgery in a Canine: A Case Report - Lehner, László; Garamvölgyi, Rita; Jakab, Csaba; Kerekes, Zoltán; Czeibert, Kálmán (Frontiers in Veterinary Science, 2019)
A 9-year-old spayed female mixed-breed dog was referred for the evaluation of intermittent head tremors, obtundation, long-standing blindness, and a tendency to seek confined spaces. The dog lost its vision 6 months before the current presentation. A menace response was absent on ophthalmological examination. Neurological examination did not show any abnormalities. A cyst measuring 16 × 18 × 14 mm was observed above the pituitary gland on magnetic resonance imaging. It extended toward the frontal area and compressed the optic chiasm and hypothalamic regions. A minimum preoperative database, including the findings of other required blood tests, was prepared. No abnormal laboratory findings were observed. Endoscopy-assisted transsphenoidal hypophysectomy was performed to remove the pituitary gland, drain the cyst, and partially excise the cyst wall. Normal pituitary gland tissue was observed on histopathology, and the mass was found to have a neuroendocrine or ependymal origin on cytology. Strict postoperative laboratory tests were performed at 1-h intervals for 24 h. An empty sella turcica region, and a collapsed and empty cyst wall was observed on follow-up magnetic resonance imaging. After 3 days of observation, the dog was discharged with a prescription of substitution therapy. However, the dog presented with the same signs and symptoms 73 days after the surgery. Cyst recurrence was apparent on magnetic resonance imaging. The owner requested euthanasia, and an ependymal cyst was observed on necropsy. To the best of our knowledge, we present the first case of an intra- and suprasellar ependymal cyst, and its surgical management in a canine. The findings from this case suggest that endoscopic transsphenoidal drainage and hypophysectomy could be a good surgical approach in cases where involvement of the pituitary gland is confirmed or strongly suspected on the basis of cytological and imaging findings.